Valorization of recyclables and sustainability evaluation: a methodological proposal for an intermediate Argentine city - Insua, Mariana Gonzalez (2024)
[Introduction]: Sustainability evaluation has been increasingly recognized as a crucial diagnostic strategy for promoting sustainable development, particularly by addressing critical environmental concerns such as urban solid waste management in Latin American cities. Within this context, situated waste management strategies focus on promoting the valorization of recyclables as a cornerstone of the circular economy and inclusive recycling initiatives. [Objective]: This study introduces a methodological framework employing a set of indicators to evaluate the valorization of recyclables across political, economic, social, and ecological dimensions of sustainability. The framework is applied specifically to Mar del Plata, Argentina, as a representative case study of an intermediate city. [Methodology]: The study adopts a systemic, interdisciplinary perspective, employing a multimethod approach that integrates primary and secondary data sources. [Results]: The proposed methodology considers four dimensions of sustainability and 18 indicators, each classified into three assessment levels. In Mar del Plata, the lowest scores are associated with source separation practices, the integration of waste pickers into the formal labor market, and the equitable distribution of power and control within the value chain at both local and global levels. [Conclusions]: The proposed indicators offer a guide for enhancing the diagnosis and management of urban solid waste in intermediate cities, focusing on the valorization of recyclables and aligning with the Sustainable Development Goals (SDGs) at the local level.